2021
DOI: 10.2147/idr.s344703
|View full text |Cite
|
Sign up to set email alerts
|

The Footprint of Diabetes Mellitus on the Characteristics and Response to Anti-Tuberculous Therapy in Patients with Pulmonary Tuberculosis from Saudi Arabia

Abstract: Background Right now, a tuberculosis (TB) and diabetes mellitus (DM) syndemic is re-emerging worldwide. Given the contradictory results of the impact of DM on the natural history of pulmonary TB (PTB), this study was undertaken to shed light on the precision of this hypothesis from a community with a substantial caseload of both diseases. Methods The present 5-year, retrospective, cohort study involved 487 (60.8% males, and 39.2% females) adult PTB patients (mean age 53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In addition, compared with the overall prevalence of DM in European patients with TB (7.5%), 6 the prevalence of DM among patients with TB in China is higher. In contrast, its prevalence is lower than that in India (28%), 20 Qatar (17%), 21 and Saudi Arabia (27.1%) 22 . This may be attributed to the effort of the Chinese National Basic Public Health Service Program, but monitoring management and public awareness still require further improvement.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…In addition, compared with the overall prevalence of DM in European patients with TB (7.5%), 6 the prevalence of DM among patients with TB in China is higher. In contrast, its prevalence is lower than that in India (28%), 20 Qatar (17%), 21 and Saudi Arabia (27.1%) 22 . This may be attributed to the effort of the Chinese National Basic Public Health Service Program, but monitoring management and public awareness still require further improvement.…”
Section: Discussionmentioning
confidence: 89%
“…29 In addition, patients with DM are more likely to have pulmonary cavities. 10,21,22 Study results have shown that abnormal opacities over the lower lung field, pulmonary cavities, and cavity nodules were more frequent among patients with TB-DM. 9 Armstrong et al found that the probability of cavitary TB was as high as 70% and the probability of smearpositive TB was as high as 50% in patients with DM according to the data shown in the 2010-2017 report of the American Tuberculosis Surveillance System.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations